(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
In a study of children with recurrent obstructive bronchitis, the effectiveness of inhaled beclamethasone was established. 54 patients with recurrent obstructive bronchitis were examined. The study showed that patients receiving inhaled beclomethasone experienced statistically significant positive dynamics in clinical symptoms, improvement in E:I index starting from the 3rd day of treatment by an average of 0.24-0.37 (P<0.05; P <0.01) until the last days of observation in comparison with patients treated according to standard protocols. Inhaled use of beclamethasone at a dose of 100 mcg/day led to a significant decrease (2.4-3.6 times) in the incidence of relapses in patients with obstructive bronchitis within 12 months after taking the drug.